360° Borescope with Adjustable LED Lighting: A Solution for Photogrammetry in Extremely Restricted Spaces - L. Barazzetti; M. Previtali; F. Roncoroni; R. Valente (The International Archives of the Photogrammetry, Remote Sensing and Spatial Information Sciences)
The system described in the paper is a prototype of a novel 360° borescope for digital documentation in confined spaces. The method was designed for both 360° inspections and photogrammetric applications in very tight and narrow spaces (even less than 30–40 cm), in which traditional digital documentation is usually impossible. The prototype is based on a panoramic camera and an integrated lighting LED system to allow for efficient image acquisition in small chambers where other documentation methods (like laser scanning and traditional photogrammetry) are not feasible due to space restrictions. Laboratory tests have demonstrated the system's capability to achieve metric precision of approximately ±1–2 cm, making it a reliable tool for confined-space documentation. By offering high-resolution imaging and the ability to generate 3D models with minimal intervention, this system represents a significant step forward in the field of confined-space documentation, with applications ranging from industrial inspections to heritage preservation.